Engineering cell signaling using tunable CRISPR–Cpf1-based transcription factors - Yuchen Liu (Nature Portfolio, 2017)
Cpf1 has been repurposed as a transcriptional repressor in bacteria and plants. Here, the authors construct activators and repressors in human cells using Cpf1 coupled to riboswitches and GPCRs.